ENVIRONMENTAL CONSEQUENCES OF ROUTINE RELEASES FROM SMALL MEDIUM REACTOR AT BABEL SITE - Udiyani Made Pande; Muhamad Budi Setiawan; Anik Purwaningsih; Nursinta Adi Wahanani; Muksin Aji Setiawan; Amir Hamzah; Hery Adrial; Jupiter Sitorus Pane (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2021)
Radiation protection and safety documents for routine conditions are required to support the licensing requirements for nuclear power plant site. This research is focused in the assessment and analysis of the results of PWR safety study related to the routine release of radioactivity from the SMR subsystems and components of the 100 MWe-type PWR along with its consequences in the site. The core inventory calculation was done using  ORIGEN2 software, applying release parameters from the existing analysis and calculation results. The radiological consequences were calculated by the PC-CREAM program package. Environmental and meteorological data were obtained using Arc-GIS and spatial analysis. The Bangka Belitung (Babel) site was used as the specific footprint. Analyzing PC-CREAM output data the radiological consequences of routine operation of 3 100 MWe PWR modules on Sebagin site (South Bangka) and Muntok site (West Bangka) in 16 sectors and within a radius of 20 km were concluded. The calculation results for the Sebagin site is that the maximumdose within a radius of 500 m (exclusion zone) is 1.15E+02 µSv/year. For a radius beyond 500 m, the maximum dose is 4.71E+01 µSv/year. Whereas for Muntok site (West Bangka), the maximum dose in the exclusion area (<500m) is 9.47E+00 µSv/year, and outside exclusion area (>500m) is 3.10E+00 µSv/year. The individual dose for the Babel site in the exclusion area is below the dose constraint for non-radiation service workers as the general public of 0.3 mSv/year or 300 µSv/year, while the maximum dose for outside exclusion is also below the constraint as stipulated in BAPETEN Regulation No 4 Year 2013 on Radiation Protection and Safety.